Efficacy and safety of dual-targeted therapy for refractory inflammatory bowel disease: a retrospective case series from three tertiary general hospitals in China - Wang, Xiaoying; Fang, Ye; Luo, Jiakai; Ye, Yongli; Li, Shuyan; Xu, Dingting; Zhang, Xiaoqi; Jiang, Yi; Yu, Qiao; Chen, Yan (Frontiers in Medicine, 2025)
AimDual-targeted therapy (DTT) may offer a promising approach for treating refractory inflammatory bowel disease (IBD). The aim of this case series was to evaluate the safety and clinical response of DTT in clinical practice.MethodsWe retrospectively analyzed data from refractory inflammatory bowel disease (IBD) patients receiving dual-target therapy (DTT) across several Chinese IBD centers. The treatment combinations included biologic agents (infliximab (IFX), adalimumab (ADA), vedolizumab (VDZ), and ustekinumab (UST) and oral small molecule tofacitinib (TOF). We collected baseline characteristics, clinical and endoscopic activity indices, inflammatory markers (C-reactive protein and albumin), and adverse events to evaluate the clinical effectiveness, endoscopic response, biochemical remission, and safety profile of DTT.ResultsA total of 8 patients with ulcerative colitis (UC) and 10 with Crohn’s disease (CD) underwent DTT at three tertiary hospitals in China. All corticosteroids initiated at baseline (six cases) were completely discontinued within 3 months. Clinical response rates were 88.23% (15/17), 91.67% (11/12), and 100% (7/7) at 3, 6, and 9 months, respectively. Endoscopic response was achieved in 88.89% (8/9) of patients who were evaluated at 9 months. Adverse events included ustekinumab-associated arthralgia and alopecia in one UC patient and tofacitinib-related allergic purpura in another, both of which were subsequently transitioned to monotherapy. Two CD patients developed infections (Clostridium difficile and bacterial intestinal infection) at 3 months, were treated with oral antibiotics, and successfully continued their original DTT regimens.ConclusionOur findings suggest that dual-target therapy demonstrates promising efficacy and an acceptable safety profile in refractory IBD patients. DTT may represent a valuable therapeutic option for patients who have not responded to conventional monotherapies.